The first technical sequences in human evolution from East Gona, Afar region, Ethiopia - de Lumley, Henry; Barsky, Deborah; Moncel, Marie Hélène; Carbonell, Eudald; Cauche, Dominique; Celiberti, Vincenzo; Notter, Olivier; Pleurdeau, David; Hong, Mi-Young; Rogers, Michael J.; Semaw, Sileshi (Antiquity, 2018)
Gona in the Afar region of Ethiopia has yielded the earliest Oldowan stone tools in the world. Artefacts from the East Gona (EG) 10 site date back 2.6 million years. Analysis of the lithic assemblage from EG 10 reveals the earliest-known evidence for refitting and conjoining stone artefacts. This new information supplements data from other Oldowan sites in East Africa, and provides an important insight into the technological capacities and evolutionary development of hominins during this period.
Keywords: East Gona; Ethiopia; Oldowan; dept.ant; knapping; peer-reviewed; refitting